2014
DOI: 10.5688/ajpe786120
|View full text |Cite
|
Sign up to set email alerts
|

Rational and Experiential Decision-Making Preferences of Third-Year Student Pharmacists

Abstract: Objective. To examine the rational (systematic and rule-based) and experiential (fast and intuitive) decision-making preferences of student pharmacists, and to compare these preferences to the preferences of other health professionals and student populations. Methods. The Rational-Experiential Inventory (REI-40), a validated psychometric tool, was administered electronically to 114 third-year (P3) student pharmacists. Student demographics and preadmission data were collected. The REI-40 results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…The outcomes demonstrated that pharmacist preferred fact, order and logic over intuition. The results are consistent with studies using the Myers-Briggs Type Indicator (Hardigan and Cohen, 1999;Shuck and Phillips, 1999;McLaughlin et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The outcomes demonstrated that pharmacist preferred fact, order and logic over intuition. The results are consistent with studies using the Myers-Briggs Type Indicator (Hardigan and Cohen, 1999;Shuck and Phillips, 1999;McLaughlin et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…As pharmacy students demonstrated rational thinking preferences. This highlighted the need to teach evidence based medicine strategies to support systematic and analytic decision making (Brown et al, 1995;McLaughlin et al, 2014;Williams et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most pharmacy students admitted to our (Table 13.2) and other schools are women (McCall et al, 2006;McLaughlin, Cox, Williams, and Shepherd, 2014), and as our data shows, this has been consistent from year to year for the past 13 years where this has been recorded within our faculty. Most pharmacy students admitted to our (Table 13.2) and other schools are women (McCall et al, 2006;McLaughlin, Cox, Williams, and Shepherd, 2014), and as our data shows, this has been consistent from year to year for the past 13 years where this has been recorded within our faculty.…”
Section: Demographic Predictorssupporting
confidence: 82%
“…These are producing a decisive demand, identifying various decisive criteria, allocating weights to each decisive criteria, developing various decisive alternatives, evaluating each decisive alternatives and selecting the best alternatives as expressed in Figure 2. In order to increase the optimization and benefits as well as decrease the uncertainty and risks in a decision-making process, the five basic assumptions have been pioneered by the Rational Decision-Making Model ("RDM") to effectively support decision-makers to reach the most suitable decision according to the Rational Behavior Theory ("RBT") [17]. These basic assumptions are (1) a decision-maker has to do the best to recognize the entirety of valid information in the decision-making process, (2) a decision-maker has to find out the entirety of decisive alternatives in association with a decisive goal [18], (3) a decision-maker is able to identify and predict the decisive outcomes of each decisive alternative under complex objective conditions [19], (4) a decision-maker is able to understand direct self-value and indirect self-experience in the decision-making process [20] and (5) a decision-maker is able to select the most optimized alternatives for achieving the maximum decisive goal [21].…”
Section: Research Interdisciplinarily Theoriesmentioning
confidence: 99%